1964
DOI: 10.1084/jem.119.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Formation and Properties of Poliovirus-Neutralizing Antibody

Abstract: The use of plaque-forming techniques in animal virology has markedly increased flae sensitivity and precision of measuring neutralizing antibody, and this together with other developments such as the ready availability of large quantities of relatively pure viral antigens and new techniques for characterizing antibody have prompted a reexamination of several aspects of the formation and properties of viral neutralizing antibody. In the work being reported a poliovirus-rabbit antibody system has been extensivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1965
1965
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Furthermore, this pattern of response is not true for all antigens, since, for example, typhoid 0 (9) and brucella (22) evoke persisting IgM antibody responses. With systems in which this sequence does occur, Uhr and Finkelstein, using OX (23), and Svehag and Mandel, using poliovirus (24,25), determined that for these antigens the IgM system does not possess immunologic memory. They showed that successive low doses of antigen elicited only brief, nonsustained IgM responses that did not increase in magnitude with repetition, whereas larger doses of antigen resulted in the above described sequential response.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this pattern of response is not true for all antigens, since, for example, typhoid 0 (9) and brucella (22) evoke persisting IgM antibody responses. With systems in which this sequence does occur, Uhr and Finkelstein, using OX (23), and Svehag and Mandel, using poliovirus (24,25), determined that for these antigens the IgM system does not possess immunologic memory. They showed that successive low doses of antigen elicited only brief, nonsustained IgM responses that did not increase in magnitude with repetition, whereas larger doses of antigen resulted in the above described sequential response.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple inoculations were necessary before satisfactory haemagglutination-inhibition titres were obtained in rabbit sera, two of the four early rabbit antisera and both early human antisera tested contained rubella-specific IgM, the presence of this class of immunoglobulin being characteristic of sera obtained shortly after a primary antigenic stimulus (Uhr & Finkelstein, ~963;Svehag & Mandel, 1964;Schluederberg, I965;Best et al I969). It has also been shown that antisera to certain arboviruses prepared in different animals and using different vaccination schedules may vary in their specificity (Saturno & Henderson,I965;Young & Johnson,I969).…”
Section: Discussionmentioning
confidence: 99%
“…5 and 6). The rate of different immunoglobulin classes (64,65) in the rate of decline of this antibody remains to be determined.…”
Section: Introductionmentioning
confidence: 99%